Role of People Opinion to Administration of Nong Waeng Kuang Sub-District Municipality, Si Somdet District, Roi Et Province - Sukmaitree, Jagraval; (Suthep Buddhachanya), Phramedhavinaiyaros; Sukontavaranon, Phrakhrupaladkaweewat Teerawit; Raggatanyoo, Salinee (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The objective of the current study is to examine the effect of people opinion in Municipality administration. The effect of Municipality administration was examined on land development, water management, waste management, cemeteries management and firefighting. Therefore, the relationship between Municipality administration, people opinion, land development, water management, waste management, cemeteries management and firefighting was examined. This relationship was examined among the community of Nong Waeng Kuang Sub-District, Si Somdet District, Roi Et Province, Thailand. Number of studies are carried out in Municipality administration; however, previous investigations have not examined the role of people opinion. Data were collected from the community of Nong Waeng Kuang Sub-District, Si Somdet District, Roi Et Province, Thailand. After the collection of data, it was analyzed by using the structural equation modeling (SEM). Findings of the study highlighted that Municipality administration has positive effect on land development, water management, waste management, cemeteries management and firefighting. Furthermore, people opinion is playing a moderating role.